Synthesis and cytotoxic activities of novel 4-methoxy-substituted and 5-methyl-substituted (3′S,4′S)-(-)-cis-khellactone derivatives that induce apoptosis via the intrinsic pathway - Chen JR; Liu JJ; Cui DX; Yan CQ; Meng LQ; Sun LQ; Ban SR; Ge R; Liang TG; Li QS (Dove Medical Press, 2017)
Jingrun Chen,1,* Junjie Liu,1,* Dongxiao Cui,1 Chaoqun Yan,1 Liqiang Meng,1 Liqian Sun,1 Shurong Ban,1 Rui Ge,1 Taigang Liang,1,2 Qingshan Li1,2 1Laboratory of Medicinal Chemistry, School of Pharmaceutical Science, Shanxi Medical University, 2College of Traditional Chinese Medicine, Shanxi University of Traditional Chinese Medicine, Taiyuan, Shanxi, People’s Republic of China *These authors contributed equally to this work Abstract: This study deals with the design and synthesis of a series of novel 4-methoxy-substituted and 5-methyl-substituted (3'S,4'S)-(-)-cis-khellactones. The newly synthesized compounds were characterized by 1H nuclear magnetic resonance (NMR), 13C-NMR, mass spectrometry, and elemental analysis. All the derivatives were subjected to in vitro cytotoxicity screening against HEPG-2 (human liver carcinoma), SGC-7901 (human gastric carcinoma), and LS174T (human colon carcinoma), by using the MTT assay. The results revealed that several of the 4-methoxy-substituted compounds exhibited potent cytotoxicity. Among these, compound 12e showed the highest activity against cancer cells which 50% inhibitory concentration (IC50) values were in the range of 6.1–9.2 µM with low toxicity on normal human hepatocyte. Preliminary investigation of possible mechanisms of action of compound 12e against HEPG-2 cells indicated possible induction of apoptosis, as determined by morphological observations and Annexin V/propidium iodide (PI) double staining, in addition to apparent dissipation of mitochondrial membrane potential (MMP), as measured by 5,5',6,6'-tetrachloro-1,1',3,3'-tetraethyl-imidacarbocyanine iodide (JC-1) staining in combination with the activation of caspase-9 and caspase-3 by Western blot analysis. Overall, the data suggest that compound 12e may be a promising potential anticancer agent that could act primarily by inducing apoptosis through the mitochondria-mediated intrinsic pathway in human hepatoma cells. Keywords: 4-methoxy-substituted and 5-methyl-substituted (3'S,4'S)-(-)-cis-khellactones, synthesis, cytotoxic activity, apoptosis